Assessing the Dimensionalities of E-Mail Utilisation Among Open and Distance Learning Practitioners in Nigeria: A Structural Modelling Equation Approach - Osang, Francis Bukie (West African Journal of Open and Flexible Learning, 2015)
The adoption and utilisation of information technologies has great impacts on productivity and performance in workplaces. In the open and distance learning environment, the utilisation of the electronic mail system by institutions of higher learning remains one viable and dependable options for an efficient communication system. But the poor usage attitude of most users within some organisations despite its availability and convenience calls for concern. Coincidentally, utilisation behaviour remains weakly conceptualised despite its critical role in the field of information systems. The data employed for the analysis were obtained through a well-designed questionnaire based on survey method administered through staff email. The respondents were chosen by purposeful sampling focusing on academic, non-academic and technical staff of the National Open University of Nigeria (NOUN) resident at both the corporate headquarters and the study centres using a sample size of 95 staff. Through a structural equation modelling (SEM) approach using smart partial least square (PLS), the sampled data were collected and analysed using the technology utilisation, satisfaction and performance model (TUSPEM) as the theoretical framework for the study. Results from the study found significant relationship between email technologies fit and staff attitude towards using the technology. The association between staff attitude towards using email system, perceived usefulness and ease of use of the technology and staff individual habit as they affect email utilisation was also supported. Testing for the fit, usefulness, ease of use of technologies, users’ attitude towards using information technologies and other critical factors using the TUSPEM model in both mandatory and non-mandatory usage environment is highly recommended. Periodic training of new and old staff on modem technologies adopted by institutions is equally recommended for improved productivity in workplaces.